Teaching HIV/AIDS through a child-to-child approach: A teacher’s perspective - Mwebi, Bosire Monari (Canadian Journal of Education/Revue canadienne de l’éducation, 2012)
This paper draws from a larger study conducted in Kenya, which was a narrative inquiry into a teacher’s experiences of teaching the HIV/AIDS curriculum using a child-to-child approach. The two major research questions of this study were: 1) What are the experiences of a teacher teaching the HIV/AIDS curriculum using a child-to-child curriculum approach? 2) What are the experiences of children learning the HIV/AIDS curriculum using a child-to-child curriculum approach? The findings suggest that a teacher who adopted a child-to-child curriculum approach in teaching HIV/AIDS experienced a transformed classroom learning environment characterized by: sharing authority with children; constructing a democratic classroom; learning to listen to children; affirming children’s voices and ownership in learning; creating a partnership with parents; interrupting gendered classroom; and developing children’s advocacy in community matters. The study concludes with recommendations for equipping teachers with the necessary skills to teach the subject. These skills are: the ability to create a child-centered classroom, ability to listen to children, ability to engage parents, and talking openly on issues about HIV/AIDS.